2017
DOI: 10.1097/jtn.0000000000000260
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Standards for Trauma Nursing Education: The Central Ohio Trauma System's Approach

Abstract: Trauma nursing requires mastering a highly specialized body of knowledge. Expert nursing care is expected to be offered throughout the hospital continuum, yet identifying the necessary broad-based objectives for nurses working within this continuum has often been difficult to define. Trauma nurse leaders and educators from 7 central and southeastern Ohio trauma centers and 1 regional trauma organization convened to establish an approach to standardizing trauma nursing education from a regional perspective. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…To address this gap, a team from Ohio convened trauma nurse leaders and educators to standardize trauma nursing education from a regional perspective (Haley et al, 2017). The team identified 42 trauma nursing educational objectives and then narrowed this to three framework objectives using a Delphi method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this gap, a team from Ohio convened trauma nurse leaders and educators to standardize trauma nursing education from a regional perspective (Haley et al, 2017). The team identified 42 trauma nursing educational objectives and then narrowed this to three framework objectives using a Delphi method.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although trauma education courses for nurses exist, trauma nursing education remains in early stages of development (Ding et al, 2016). One of trauma nursing education's biggest challenges is the lack of clearly defined national standards (Haley et al, 2017). The American College of Surgeons' (2014) Resources for Optimal Care of the Injured Patient indicates that Level I, II, and III trauma centers “must provide a mechanism to offer trauma-related education to nurses involved in trauma care” (p. 190); however, educational concepts and objectives are not defined within the ACS directive.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it appears that ED nurses at PHN hospital face difficulties in attending trauma courses. Factors such as the availability of courses, the high cost, and workload, may hinder ED nurses from attending trauma courses (49) .…”
Section: Discussionmentioning
confidence: 99%
“…Schultz et al 15 developed a core competency teaching system for acute care physicians, nurses and Emergency Medicine Service System professionals based on knowledge, skills and attitudes, but only part of it is appropriate for emergency trauma nurses. Haley et al 16 identified 42 trauma nursing educational objectives, such as trauma assessment and nursing intervention, but failed to build a complete training system. In China, one pressing concern is the lack of a trained workforce to meet the complex needs of emergency trauma patients, and many emergency trauma patients receive care from an undefined workforce, including nurses 17.…”
Section: Introductionmentioning
confidence: 99%